Demographic and behavioral characteristics of urban and non-urban PrEP-using MSM in the South. Issue 11 (2nd November 2022) - Jones, Jeb; Pampati, Sanjana; Emrick, Kayla; Siegler, Aaron J.
ABSTRACT: Pre-exposure prophylaxis (PrEP) is a highly effective HIV prevention intervention; however, most studies of PrEP adherence and persistence among men who have sex with men (MSM) have been conducted with MSM who live in urban areas. The experiences of PrEP-using MSM in non-urban areas might differ due to increased barriers to culturally competent care. We examined similarities and differences among urban and non-urban PrEP-using MSM in the southern United States, the region with the highest number of annual HIV diagnoses. We surveyed a total of 78 ( n = 25 non-urban, n = 53 urban) PrEP-using MSM. Self-reported adherence was high across all participants. No differences were observed with respect to PrEP persistence, source of PrEP, or reasons for PrEP initiation. Fewer non-urban than urban men reported STI testing in the past 12 months. Overall, we observed few differences comparing urban and non-urban PrEP-using MSM. Additional studies are needed to describe differences in PrEP initiation comparing urban and non-urban MSM.